Performance study of ZnO-TPU/CS bilayer composite electrospinning scaffold in skin wound healing - Wang, Jinlong; Huang, Guoxing; Qin, Quan; Dan, Nianhua; Li, Xinlou; Sun, Kai; Yang, Yuan; Wang, Meng (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThe high incidence of skin injuries and the limitations of conventional dressings highlight the need for advanced wound care materials. Electrospun nanofibrous scaffolds, with their extracellular matrix-like architecture, offer potential to enhance healing.MethodsA bilayer nanofibrous scaffold of thermoplastic polyurethane (TPU) and chitosan loaded with zinc oxide nanoparticles (ZnO) (TPU/CS@ZnO) was fabricated via electrospinning. The scaffold consisted of a hydrophobic TPU outer layer for waterproof protection and a hydrophilic TPU/CS@ZnO inner layer for bioactivity. Physicochemical properties were characterized by morphology, mechanical strength, and wettability. Cytocompatibility was evaluated in vitro, and wound healing efficacy was tested in vivo using a full-thickness skin defect model.ResultsThe scaffold displayed uniform fibres with a base-layer diameter of 231.81 ± 44.85 nm, tensile strength of 8.42 ± 0.58 MPa, and Young’s modulus of 17.96 ± 0.78 MPa. Water contact angles confirmed hydrophilic and hydrophobic layer characteristics (52.68° ± 4.46° vs. 113.60° ± 2.85°). In vitro studies showed enhanced cell proliferation and adhesion, while in vivo experiments demonstrated over 90% wound closure at day 14, significantly faster than untreated groups. Histological analysis indicated contributions from cellular adhesion, angiogenesis, and immunomodulation.DiscussionThe bilayer TPU/CS@ZnO scaffold integrates structural protection with biological activity, accelerating wound repair through multiple mechanisms. These findings support its potential as a multifunctional wound dressing, while further studies are needed to clarify molecular pathways and advance clinical application.